2021
DOI: 10.1109/jsyst.2020.2996909
|View full text |Cite
|
Sign up to set email alerts
|

MmWave Beam Management in Urban Vehicular Networks

Abstract: Mmwave bands are being widely touted as a very promising option for future 5G networks, especially in enabling such networks to meet highly demanding rate requirements. Accordingly, the usage of these bands is also receiving an increasing interest in the context of 5G vehicular networks, where it is expected that connected cars will soon need to transmit and receive large amounts of data. Mmwave communications, however, require the link to be established using narrow directed beams, to overcome harsh propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…strongly influenced by the adopted beamforming architecture (see e.g., [31]), in this work we consider α ST MIN = α TL MIN = 3 • , due to the following reasons. First, such setting is in line with other relevant works targeting beam management in 5G networks (see e.g., [32]). Second, it is expected that 5G gNB adopting pencil beamforming will be able to synthesize very narrow traffic beams (i.e., in the order of few degrees).…”
Section: Scenario Descriptionsupporting
confidence: 58%
“…strongly influenced by the adopted beamforming architecture (see e.g., [31]), in this work we consider α ST MIN = α TL MIN = 3 • , due to the following reasons. First, such setting is in line with other relevant works targeting beam management in 5G networks (see e.g., [32]). Second, it is expected that 5G gNB adopting pencil beamforming will be able to synthesize very narrow traffic beams (i.e., in the order of few degrees).…”
Section: Scenario Descriptionsupporting
confidence: 58%
“…We assume that all the BSs are equipped with N isotropic active elements for beamforming towards the targets while the UEs are equipped with single omnidirectional antenna. Furthermore, the recent works in [47], [49] have shown that the empirical distribution of small-scale fading effects of the channel and the beamforming gain of the antenna array can be tightly approximated by using exponential distribution. Thus, in order to maximize the mathematical tractability of our analysis, we consider the following assumption for the small-scale fading channel gain.…”
Section: System Modelmentioning
confidence: 99%
“…Assumption 1 (Small-Scale Channel Gain): The smallscale fading gain is assumed to follow an exponential distribution with mean of 1/µ. In the past, this assumption was common in stochastic geometric coverage analysis for mathematical tractability [6], [47], [49]- [53]. Recent works [47], [49] revisited this exponential fading assumption, and rediscovered its feasibility even under realistic large-scale mmWave systems, by simply tuning µ according to the mean channel characteristics and antenna patterns.…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in ultra dense scenarios, a narrow beam can cover several users simultaneously, users that can be multiplexed within the same beam. There are only few works that consider that a mmWave link can be used to establish communication with several end users simultaneously [22], [23]. In particular, [22] considers a dense urban scenario, and uses traffic light information to guide the beam directions chosen by the infrastructure nodes; however, [22] does not consider coordination between nodes as we do in this work.…”
Section: Related Workmentioning
confidence: 99%